The impact of bitcoin futures trading on cryptocurrency spot prices - Sukumaran, Shankara (2022)
This research examines the impact of Bitcoin futures trading on six different cryptocurrencies spot prices using EGARCH. Additionally, this research examines the existence of leverage effect and symmetric effect in the event of an unanticipated price movement by conducting a time-varying analysis for six cryptocurrencies. Using adjusted closing price data from 1st January 2015 to 1st January 2021 this research revealed that Bitcoin, Ripple, and Dogecoin destabilised after the launch of Bitcoin futures while Ethereum, Litecoin, and Monero stabilized. These results remain robust to tests conducted with a simple GARCH model. Additionally, the time-varying analysis discovered evidence of a low leverage effect on all six cryptocurrencies in the post-futures period. The analysis also demonstrates that the symmetric impact outweighs the leverage effect for all six cryptocurrencies. By comparing the EGARCH parameter across the pre-futures and post-futures period, it is found that except for Ripple and Dogecoin all other cryptocurrencies has a strong positive leverage effect in the pre-futures period and negative leverage effect in the post-futures period. Dogecoin appears to be distinctive, with high leverage effects in the post-futures period. Finally, this research discovered that Ripple's positive leverage decreases in the post-futures period, while Dogecoin's positive leverage increases.